FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN SUKARELA PELAPORAN KEUANGAN DAN KEBERLANJUTAN MELALUI INTERNET DAN IMPLIKASINYA TERHADAP ASIMETRI INFORMASI - Maulana Fajri Al Arafi; Sutrisno T (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research aims to find empirical evidence about the effect of firm size, profitability, leverage and non-management share ownership portion to internet financial and sustainability reporting, as well as to find empirical evidence about the effect of internet financial and sustainability reporting to information asymmetry. The population in this research are 446 Indonesian companies listed in Indonesian Stock Exchange (IDX) in period 2012. This research selected 120 companies by using non-probability random sampling (purposive sampling). These research data were analyzed using multiple regression analysis and simple regression analysis. The results indicated that firm size and profitability had influence on internet financial and sustainability reporting. The research also showed that internet financial and sustainability reporting could reduce information asymmetry. Keywords: Internet Financial and Sustainability Reporting, Firm Size, Profitability, Leverage, Non-management Share-ownership portion, Information Asymmetry.